Relationship between nutritional status and mortality during the first 2 weeks following treatment for cervical spinal cord injury. (January 2014) - Chen, Xiaobin; Liu, Zhi; Sun, Tiansheng; Ren, Jixin; Wang, Xiaowei
Abstract : Background: The effects of nutrition on the mortality of cervical spinal cord injury (CSCI) patients, unlike other risk factors, are poorly documented. Objective: The relationship between dynamic nutritional status change and mortality in patients treated for CSCI was investigated. Methods: A retrospective study of 128 patients treated for CSCI at the Beijing Army General Hospital was conducted between March 2006 and March 2011. Age, spinal segment damage (C1–C4 and C5–C7), American Spinal Injury Association (ASIA) grade, hospitalization duration, ventilatory support, and serum protein levels (total protein, serum albumin, and serum prealbumin) were assessed during early-stage treatment (<14 days). Survival ( n = 109) and death ( n = 19) groups were assigned by final disposition of acute hospitalization. Results: The survival group evidenced no significant changes in total protein levels during early-stage treatment, although these values decreased in the death group. Serum prealbumin and albumin levels significantly declined by treatment day 1 and throughout treatment ( P < 0.05). By days 3–5 and thereafter, significantly lower serum proteins were observed in the death group compared to the survival group ( P < 0.05). Multiple segment damage, elevated ASIA, and longer ventilatory support duration were more prevalent in the death group ( P < 0.001) Conclusions: Lower serum protein levels associated with hypoproteinemia and malnutrition are significant indicators of mortality in patients with CSCI, along with higher levels of lesions, elevated ASIA grades, and longer ventilatory support durations. Early corrective action for hypoalbuminemia may help to reduce mortality in patients with CSCI.